2023
DOI: 10.1038/s41598-023-49353-1
|View full text |Cite
|
Sign up to set email alerts
|

Robust acceleration of Earth system heating observed over the past six decades

Audrey Minière,
Karina von Schuckmann,
Jean-Baptiste Sallée
et al.

Abstract: Global heating of the Earth system is unequivocal. However, detecting an acceleration of Earth heating has remained elusive to date, despite suggestive evidence of a potential increase in heating rates. In this study, we demonstrate that since 1960, the warming of the world ocean has accelerated at a relatively consistent pace of 0.15 ± 0.05 (W/m2)/decade, while the land, cryosphere, and atmosphere have exhibited an accelerated pace of 0.013 ± 0.003 (W/m2)/decade. This has led to a substantial increase in ocea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The contributions to increases in the Earth heat inventory throughout 1971-2018 remained stable: 91 % for the full-depth ocean, 5 % for the land, 3 % for the cryosphere and about 1 % for the atmosphere (Forster et al, 2021). Two recent studies demonstrated independently and consistently that since 1960, the warming of the world ocean has accelerated at a relatively consistent pace of 0.15 ± 0.05 W m −2 per decade (Minière et al, 2023;Storto and Yang, 2024), while the land, cryosphere, and atmosphere have exhibited an accelerated pace of 0.013 ± 0.003 W m −2 per decade (Minière et al, 2023). The increase in EEI over the most recent quarter of a decade (Fig.…”
Section: Earth Energy Imbalancementioning
confidence: 86%
“…The contributions to increases in the Earth heat inventory throughout 1971-2018 remained stable: 91 % for the full-depth ocean, 5 % for the land, 3 % for the cryosphere and about 1 % for the atmosphere (Forster et al, 2021). Two recent studies demonstrated independently and consistently that since 1960, the warming of the world ocean has accelerated at a relatively consistent pace of 0.15 ± 0.05 W m −2 per decade (Minière et al, 2023;Storto and Yang, 2024), while the land, cryosphere, and atmosphere have exhibited an accelerated pace of 0.013 ± 0.003 W m −2 per decade (Minière et al, 2023). The increase in EEI over the most recent quarter of a decade (Fig.…”
Section: Earth Energy Imbalancementioning
confidence: 86%
“…The overall low (165 years) and temporally fading (up to 184 years) resolution of the global proxy network, plus the generally high and temporally increasing dating uncertainty characteristic to many of the records (schematically illustrated in Figure 5), massively mutes the variability in Holocene GST reconstructions derived from these data, and obscures any comparison with modern-day, short-term, temperature observation [25,26]. We therefore argue that comparisons of decadal-scale instrumental GSTs with centennialscale proxy-derived GSTs, as included in the IPCC Technical Summary, are of limited meaning.…”
Section: Consequences For Modern-day Analogsmentioning
confidence: 99%